2023
DOI: 10.1002/ar.25155
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of CD146 and alpha‐smooth muscle actin during dentin formation and regeneration

Abstract: Cluster of differentiation 146 (CD146) is known to localize in stem cells and precursor cells of various tissues. In this study, to analyze the function of CD146 in odontoblast differentiation, immunohistochemical localization of CD146 was examined during rat molar tooth development and after cavity preparation. At the cap and bell stages, many CD146‐positive cells were visible around the blood vessels in the dental papillae. On Postnatal day 2, osterix‐positive odontoblasts were arranged in the dentin sialopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…α-SMA is a cytoskeletal protein that is also localized in some stem cells and precursor cells and is considered to be one of the stem cell markers in dental pulp. α-SMA is also expressed in vascular pericytes, myofibroblasts and smooth muscle cells, and plays a key role in wound healing and participates in dental pulp healing [ 22 ]. During dentin formation, the majority of MSCs were identified to be located in the perivascular area, which is considered as a stem cell niche [ 23 ], and in this study, α-SMA positive cells were observed in the perivascular area.…”
Section: Discussionmentioning
confidence: 99%
“…α-SMA is a cytoskeletal protein that is also localized in some stem cells and precursor cells and is considered to be one of the stem cell markers in dental pulp. α-SMA is also expressed in vascular pericytes, myofibroblasts and smooth muscle cells, and plays a key role in wound healing and participates in dental pulp healing [ 22 ]. During dentin formation, the majority of MSCs were identified to be located in the perivascular area, which is considered as a stem cell niche [ 23 ], and in this study, α-SMA positive cells were observed in the perivascular area.…”
Section: Discussionmentioning
confidence: 99%